Sexual Concerns of Patients With Implantable Left Ventricular Assist Devices. Issue 8 (6th July 2015) - Merle, Pascal; Maxhera, Bujar; Albert, Alexander; Ortmann, Philipp; Günter, Mareile; Lichtenberg, Artur; Saeed, Diyar
Abstract The growing field of implantable left ventricular assist devices (LVADs) lacks studies that evaluate the sexual and psychosocial concerns of LVAD patients. The aim of this prospective study was to determine the sexual and psychosocial behaviors of these patients. A sexual and psychosocial survey was conducted in patients who underwent the implantation of LVAD. Inclusion criteria were patients who were discharged home. The survey consisted of 17 questions with main focus on the sexual life and activities. The survey was sent to 38 patients. Twelve patients had either no partners or did not respond to the survey. Data of the remaining 26 patients with a mean age of 54 ± 13 years old were analyzed. The mean time between LVAD implantation and the first sexual activity was 16 ± 13 weeks (6–42 weeks). Following LVAD implantation, there was a steady improvement in the physical condition and quality of life. However, a remarkable decrease in the degree of satisfaction with sexual life following LVAD implantation (5.5 ± 2.2 vs. 4.1 ± 2.5) was observed (P = 0.05) (a scale of 1–7, with 7 being very satisfied and 1 not satisfied). Decreasing sexual activities after LVAD implantation was mainly to avoid partner disappointment, sudden cardiac arrest, and LVAD failure. There is a notable reduction in the degree of satisfaction with sexual life after LVAD implantation. The majority of the patients avoid discussing this issue with their physicians. Psychological and psychosocial support of LVAD patients is mandatory to improve their life quality.